2010
DOI: 10.1128/aac.00057-10
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Analysis of Divergence of Antibiotic Resistance Determinants in Closely Related Isolates of Acinetobacter baumannii

Abstract: Multidrug resistance has emerged as a significant concern with infections caused by Acinetobacter baumannii. Ample evidence supports the involvement of mobile genetic elements in the transfer of antibiotic resistance genes, but the extent of variability and the rate of genetic change associated with the acquisition of antibiotic resistance have not been studied in detail. Whole-genome sequence analysis of six closely related clinical isolates of A. baumannii, including four from the same hospital, revealed ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 41 publications
4
94
0
Order By: Relevance
“…In support of these observations, Adams et al (2) similarly found variability in resistance genes associated with insertion sequences, plasmids, and the AbaR chromosomal resistance gene island among closely related clinical isolates of A. baumannii. Some of the differences between isolates were of a more general nature, such as the association of cusS with representatives of international clone I (and III) but not with those of international clone II.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In support of these observations, Adams et al (2) similarly found variability in resistance genes associated with insertion sequences, plasmids, and the AbaR chromosomal resistance gene island among closely related clinical isolates of A. baumannii. Some of the differences between isolates were of a more general nature, such as the association of cusS with representatives of international clone I (and III) but not with those of international clone II.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, a number of "AbaR"-type resistance islands, inserted in an ATPase gene (here called comM) and carrying genes associated with resistance to antibiotics and heavy metals, have been described previously (1,2,11,16,17,20,21). The latter show diversity, with that described in an isolate of international clone II (AbaR2 in ACICU) being considerably smaller than that found in isolates of international clone I; among the latter, a number of different islands have already been described.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Patient 4, who had a prolonged stay in ICU A during the outbreak, harbored isolates both with and without this plasmid. Although plasmids have been shown to be important in the dissemination of antibiotic resistance during outbreaks (80,81), they are of limited value for defining transmission pathways, because they are frequently gained and lost by closely related circulating strains (74, …”
Section: Resultsmentioning
confidence: 99%
“…Mobile elements and resistance determinants associated to antibiotic resistance have been well studied for A. baumannii [10][11][12], in contrast there are few reports of these elements in A. junii [13,14].…”
Section: Introductionmentioning
confidence: 99%